Mapping the landscape of recent research on agricultural geography (2013–2022) - Sai-Leung Ng; Ching-Hua Tien (Acta Geographica Slovenica, 2024)
Agricultural geography has developed for over a century. To review the recent development in this field, 1879 journal articles on agricultural geography published between 2013 and 2022 are analyzed using multi-leveled bibliometric methods and visualized by VOSviewer. Seven research themes are identified: “climate change and food”, “environmental sustainability”, “land and political ecology”, “water resources”, “rural geography”, “economic development”, and “spatial analysis”. Theory and practice are the two research strands, with few authors publishing extensively, indicating a lack of an active long-term research community. Geographical factors significantly influence agricultural geography research, with international collaborations showing regional patterns. China is an emerging player, developing independently from Western peers.